2016
DOI: 10.7717/peerj.2671
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide induced loss of heterozygosity correlates with replicative lifespan and mitotic asymmetry inSaccharomyces cerevisiae

Abstract: Cellular aging in Saccharomyces cerevisiae can lead to genomic instability and impaired mitotic asymmetry. To investigate the role of oxidative stress in cellular aging, we examined the effect of exogenous hydrogen peroxide on genomic instability and mitotic asymmetry in a collection of yeast strains with diverse backgrounds. We treated yeast cells with hydrogen peroxide and monitored the changes of viability and the frequencies of loss of heterozygosity (LOH) in response to hydrogen peroxide doses. The mid-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Most previous studies have shown that H 2 O 2 treatment elevates mitotic recombination (9,10,41,42). These studies are difficult to compare directly with the current study since recombination was assayed by different methods.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have shown that H 2 O 2 treatment elevates mitotic recombination (9,10,41,42). These studies are difficult to compare directly with the current study since recombination was assayed by different methods.…”
Section: Discussionmentioning
confidence: 99%